Organization-stakeholder fit: A dynamic theory of cooperation, compromise, and conflict between an organization and its stakeholders - Bundy, Jonathan; Vogel, Ryan M.; Zachary, Miles A. (Strategic Management Journal, 2018)
[Research summary: We advance the concept of organization-stakeholder fit (O-S fit) to explain cooperative behavior between an organization and its stakeholders. O-S fit describes the compatibility that exists between an organization and a stakeholder when their characteristics are well matched. We highlight two dimensions of O-S fit: value congruence, or the supplementary fit of organizational and stakeholder values, and strategic complementarity, or the complementary fit of strategic needs and resources. For each dimension, we detail the unique relational factors—including core elements of trust, predictability, attraction/exchange, and communication—that motivate cooperation. We then explicate the ways in which value congruence and strategic complementarity dynamically interrelate over time. Finally, we consider how organization-stakeholder misfit may result in alternative relational behaviors, such as conflict or compromise. Managerial summary: We develop a new way of thinking about the relationship between organizations and stakeholders. Recognizing that positive relationships require a degree of fit or compatibility, we argue that cooperative behavior between an organization and its stakeholders is maximized when relational partners share both core values and strategic priorities. We explain that high fit along these two dimensions increases trust, relational predictability, attraction/exchange, and communication. We also describe how positive relationships might be formed with fit along only one dimension, and how negative relationships might result in the presence of misfit. Ultimately, we suggest that managers who want to foster positive relationships with stakeholders should concentrate on aligning their values and priorities, rather than simply concentrating on one or the other.]